The application of computing technology to interpersonal communication at the University of Dundee's Department of Applied Computing. - Gregor P; Alm N; Arnott J; Newell AF (Technology & Disability, 1999)
This paper provides an overview of the major areas of research within the Department of Applied Computing at the University of Dundee. This research focuses on the areas of Interactive Communication Systems, Telecommunications and Remote Learning, Computer based Interviewing and Knowledge Elicitation, Health Informatics, Software Engineering, and Digital Signal Processing. A major strand throughout these areas is a focus on Human Computing Interaction issues, and the use of computing technology to facilitate interpersonal communication, particularly for people with disabilities. The research has produced many new insights in these areas and a number of commercial products have been licensed as a result. The Department's unique approach is based on placing the user at the centre of the design process, and having people with disabilities make major contributions as participants in the research and also as researchers.